The European Court of Human Rights, Amicus Curiae, and Violence against Women. Issue 4 (7th November 2016) - Cichowski, Rachel A.
Abstract : Are international courts and advocacy group legal mobilization shaping human rights politics? This question poses a theoretical and empirical challenge to state dominated understandings of international litigation. This article theorizes the interaction between advocacy groups and the European Court of Human Rights and the role this participation plays in the enforcement and development of human rights. The analyses examine institutional factors shaping broad trends in mobilization complemented by two in depth studies examining a single mode of participation, amicus curiae and a single area of law, violence against women. The data identify the critical role standing rules, court review powers and group expertise play in transnational rights mobilization and development. The findings bring into question dominant understandings of international law and contribute to a more complex understanding of law in a global age where international courts and societal actors are shaping the direction of rights protection.